ВИЗНАЧЕННЯ ТЕПЛОФІЗИЧНИХ ХАРАКТЕРИСТИК ВУГЛЕЦЬ-ВУГЛЕЦЕВОГО МАТЕРІАЛУ ВВКМ-21 РОЗРАХУНКОВО-ЕКСПЕРИМЕНТАЛЬНИМ МЕТОДОМ - Borovyk, D.V.; Yevdokymenkо, Yu.I.; Krukovsky, P. G.; Frolov, G.O.; Skliarenko, D.I. (Institute of Engineering Thermophysics of NAS of Ukraine, 2024)
The continuous improvement of thermal protection efficiency for rocket and space technology (RST) components is a key aspect of progress in this field. Today, carbon-carbon composite materials (CCCM) are increasingly becoming the standard in thermal protection systems. Simultaneously, CCCMs are being used more frequently in devices for testing RST materials and evaluating component durability. For instance, CCCMs serve as structural and heating elements in vacuum furnaces under high mechanical and thermal loads. The expanding application of such materials requires enhancements to existing methods and the development of new approaches for studying and determining their thermophysical properties. This paper addresses this need by investigating heat propagation in flat CCCM samples with different fiber orientations in the matrix using a combined experimental-computational method to determine their heat capacity and thermal conductivity in the temperature range of 300–1200 K. The study involved furnace heating of CCCM samples, with the selected temperature range justified by the onset of thermoerosion at 1200 K for CCCMs. Temperatures up to 1200 K with heating durations of up to 60 seconds typically do not cause significant surface degradation. Heat capacity was determined at temperatures up to 700 K using the IT-с-400 device and calculated up to 2000 K using the «ASTRA 4.0» software. Thermal conductivity was obtained through a computational-experimental approach, employing a heat conduction model and an inverse problem methodology. Experimental temperatures from two surfaces of a flat sample during one-sided heating were used to solve the inverse problem. The COMSOL Multiphysics® software package, an integrated platform for modeling physical processes (including heat transfer) in environments and objects of various geometries, was employed for the calculations.